In vitro study of nano-hydroxyapatite/chitosan–gelatin composites for bio-applications - Khaled R. Mohamed; Hanan H. Beherei; Zenab M. El-Rashidy (Journal of Advanced Research, 2014)
The present work aims to study the in vitro properties of nano-hydroxyapatite/chitosan–gelatin composite materials. In vitro behavior was performed in simulated body fluid (SBF) to verify the formation of apatite layer onto the composite surfaces. The in vitro data proved the deposition of calcium and phosphorus ions onto hydroxyapatite /polymeric composite surfaces especially those containing high concentrations of polymer content. The degradation of the composites decreased with increase in the polymeric matrix content and highly decreased in the presence of citric acid (CA), especially these composites which contain 30% polymeric content. The water absorption of the composites increased with increase in the polymeric content and highly increased with CA addition. The Fourier transformed infrared reflectance (FT-IR) and scanning electron microscope (SEM) for the composites confirmed the formation of bone-like apatite layer on the composite surfaces, especially those containing high content of polymers (30%) with 0.2 M of CA. These promising composites have suitable properties for bio-applications such as bone grafting and bone tissue engineering applications in the future.